Establishment of Pediatric Medication Therapy Management: A Proposed Model - Sandra Benavides; Shirin Madzhidova; Anihara Hernandez; Thao Le; Stephanie M. Palma; Steffi Stephen (MDPI AG, 2016)
Ongoing healthcare reform calls for increased accessibility, enhanced delivery, and improved quality of healthcare. Children and adolescents are experiencing a rise in the prevalence in chronic diseases leading to an increased utilization of medications. The increased use of chronic medications can lead to more medication errors or adverse drug events, particularly in children and adolescents using multiple chronic medications. These ongoing changes expand opportunities for a pharmacist to become further integrated in the inter-professional healthcare delivery for pediatric patients, particularly in an ambulatory or community setting. To date, a systemic process for the provision of medication therapy management (MTM) services in pediatric patients has not been elucidated. The purpose of this paper is to describe a proposed model for delivering pediatric MTM. Furthermore, based on the available literature related to pediatric patients at risk for medication errors, adverse drug reactions, and subsequently-increased utilization of emergency departments and hospitalizations, a set of criteria is proposed for further research investigation.